Perceived stress among students in virtual classrooms during the COVID-19 outbreak in KSA - Deemah A. AlAteeq, MBBS; Sumayah Aljhani, MBBS; Dalal AlEesa, MBBS (Journal of Taibah University Medical Sciences, 2020)
الملخص: أهداف البحث: كوفيد-١٩ هو مرض فيروس كورونا المعدي المستجد الذي أصبح مؤخرا جائحة. نظرا لأن تفشي المرض يمكن أن يكون له عواقب على الصحة النفسية، فقد هدفت هذه الدراسة إلى استكشاف مستوى التوتر النفسي بين الطلبة أثناء تفشي مرض فيروس كورونا المستجد وتعليق التعليم التقليدي في المملكة العربية السعودية. طرق البحث: أجريت هذه الدراسة المقطعية لعينة تتكون من ٣٦٧ طالبا وطالبة يعيشون في المملكة العربية السعودية، حيث تم تقييم الخصائص الاجتماعية والديموغرافية، والتوتر النفسي، والمشاعر والمخاوف أثناء تفشي المرض. النتائج: غالبية المشاركين من الإناث (٧٤.٧٪)، وفي المرحلة الدراسية الثانوية (٧٩.٨٪). أظهر أكثر من نصف المشاركين مستويات توتر متوسطة (٥٥٪)، وأظهر ٣٠.٢٪ منهم توترا مرتفعا. كما ظهر ارتباط ملحوظ بارتفاع مستوى التوتر لدى الطالبات الإناث وطلبة المرحلة الجامعية. الاستنتاجات: هناك مستويات عالية إلى معتدلة من التوتر النفسي لدى الطلبة في المملكة العربية السعودية أثناء فترة بداية فترة تفشي مرض فيروس كورونا مع ارتفاع خطورة التوتر عند الطالبات الإناث وعند طلبة المرحلة الجامعية. قد يكون من المفيد دمج الاستشارات عبر الانترنت وبرامج إدارة التوتر مع عملية التعليم عن بُعد. Abstract: Objectives: COVID-19 is a newly discovered infectious Coronavirus that became pandemic. Since disease outbreaks can have mental health consequences, this study explored the perceived stress level among students during the Coronavirus Disease Outbreak and suspension of in-person teaching in Saudi Arabia. Methods: A cross-sectional survey of a sample consisting of 367 students living in Saudi Arabia assessed socio-demographic characteristics, Perceived Stress Scale (PSS) and their emotions and concerns during the outbreak. Results: Most participants were female (74.7%) and secondary school (79.8%) students. More than half of the participants showed moderate levels of stress (55%), while 30.2% registered high levels. Females and university students showed a significant association with stress level (p-value = 0.003 and 0.049, respectively). Conclusions: There was a moderate to high level of stress among students in KSA at the start of the COVID-19 outbreak. This study found a significant correlation between a high level of stress and female university students. The integration of online counselling and stress management programs would help mitigate the stress of students during distance learning.